Problematic of Lorentz -Einstein’s Transformations - Al-Tamimi, Mohammad (Advances in Social Sciences Research Journal, 2021)
When I tried to derive which was used by Lorentz in his transformations, I found it has a different value. Also the same problem happened with was used by Einstein in equations of the special theory of relativity (STR). To explain this problematic, I tried to apply these transformations to a perfect and real relativistic experiment where I proved this real problematic, that confused physical society for decades. Indeed, I strongly believe that, this problematic is coming as a reflection of the conception of the velocity law on STR where, we can’t build this conception on the bending of the dimensions of the spacetime.